SYNTHESIS OF NANO-SILICA FROM LOA KULU RICE HUSK USING THE SOL-GEL METHOD - Shoodiqin, Dian Mart; Musyarofah, Musyarofah; Robiandi, Fadli; Chairunnisa, Regita Cahya (Indonesian Physical Review, 2024)
Silica is a material that is widely found in nature and is able to withstand corrosion attacks from corrosive environments. However, this natural material must be extracted to obtain high purity silica. Simple sol-gel method is used to solve the extraction problem (nano-silica with high purity). The natural materials used in this research come from organic materials, namely rice husks from the local area (Loa Kulu area). The main objective of this experiment is studying the effect concentration of HCl for crystalline size.  The synthesis of silica was carried out with the preparation of ashes, then mixed with NaOH 7M until a solution of sodium silicate was produced. Silicate sodium solution was pressed with HCl 2M to form a silica gel with pH 7, 5, and 3 then was dried to produce silica powder. Silica powder was then burned at a temperature of 1000°C to produce silica with a crystalline phase. Based on the experiment, silica powder before calcination has amorphous phase and at any pH variation, the crystallite size calculated with the Debye Scherrer approach does not show any change the crystallite size by the variation of the silica gel’s pH. In addition, silica powder calcinated at 1000°C has amorphous and cristobalite phases and showed changes in crystal size after calculated with Debye Scherrer’s approach.